Analisis Implementasi Kebijakan Reforma Agraria dalam Mendukung Ketahanan Nasional - Slamet Riswanto; Hikmat Zakky Almubarroq; Edy Saptono (CV. AFDIFAL MAJU BERKAH, 2024)
Agrarian reform is a strategic policy that aims to redistribute land to the community, tiny farmers, and tenants to reduce land ownership inequality and improve people's welfare. Land inequality in Indonesia is very high, with the land tenure Gini index reaching 0.68, higher than the income Gini index, which stands at 0.388. This inequality not only creates socio-economic problems such as poverty and agrarian conflict but also impacts national resilience. This research uses SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to evaluate the implementation of agrarian reform policy and determine the right strategy to accelerate its implementation in supporting national resilience. This analysis identifies several strengths in the agrarian reform policy, such as government commitment and adequate infrastructure support. However, areas for improvement, such as lack of optimization of access to agrarian reform programs and slow resolution of land disputes, were also found. Opportunities include community empowerment and increased economic resources, while threats come from resistance from parties with specific interests and challenges in land redistribution. The results of this analysis are expected to provide strategic recommendations to improve the implementation of agrarian reform policies, such as strengthening cross-sectoral cooperation, increasing socialization and training, and improving access to information for the community. Thus, an effective agrarian reform program is expected to enhance community welfare and contribute to national resilience.